Problem-Based Learning in Counsellor Education - Stewart, John B. (Canadian Journal of Counselling and Psychotherapy, 2007)
In this article, the author discusses the principles o f problem based learning and their application to graduate level counsellor education. Problem-based learning is an educational approach using a problem statement, around which new information and skill development is initiated via a process which utilizes professional critical thinking and reasoning skills. Using this approach, counsellor education programs can be conceptualized around three phases: an essential theory and skills phase accenting broad theoretical parameters and skill development; a problem-based learning phase integrating additional information using critical thinking and reasoning skills; and an internship phase where students apply their learning in a professional context.